2004
DOI: 10.1002/sim.1611
|View full text |Cite
|
Sign up to set email alerts
|

Confidence intervals for the effect of a prognostic factor after selection of an ‘optimal’ cutpoint

Abstract: When investigating the effects of potential prognostic or risk factors that have been measured on a quantitative scale, values of these factors are often categorized into two groups. Sometimes an 'optimal' cutpoint is chosen that gives the best separation in terms of a two-sample test statistic. It is well known that this approach leads to a serious inflation of the type I error and to an overestimation of the effect of the prognostic or risk factor in absolute terms. In this paper, we illustrate that the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 30 publications
0
54
0
3
Order By: Relevance
“…We used a multivariate Cox proportional hazards model to determine HRs. HRs were corrected as suggested by Holl€ ander and colleagues (20). All tests were two-sided, and a P < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…We used a multivariate Cox proportional hazards model to determine HRs. HRs were corrected as suggested by Holl€ ander and colleagues (20). All tests were two-sided, and a P < 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this strategy has already been illustrated [39], and presents the advantage of simplified computations and interpretation of results, in the case of a substantially large population sample. Some authors have suggested selecting optimal cut-points by the use of cross validation procedures [34], bootstrapping computations of an optimal cut-point effect confidence interval [40,41], adjusted significance level tests [34,42] and multivariate settings [43]. However, loss of power [34,43] and underestimated HR [34] have been reported in the case of the cross validation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The serum GSTP1 hypermethylation status was coded as a categorical variable in this analysis. The optimal cut point for total DNA in the multivariable model was chosen using the minimum P value method with bootstrap resampling to correct for overfitting (18). For the multivariate analysis, we used the significant variables from the univariate model: total DNA level, surgical margin status, and lymph node status.…”
Section: Methodsmentioning
confidence: 99%